Yorgus Yogurt and Zona Sul : building a new venture in an established family business - Pendergas, Jennifer; Craig, Justin B.; Waikar, Sachin (London : Kellogg School of Management, 2022)
Yorgus, a Brazilian entrepreneurial maker of premium Greek yogurt, has hit its stride--and now it faces questions about the best path to achieve growth, including becoming independent of the context in which it was created. Founder Enrico Leta launched the company in mid-2014, and Yorgus grew against the backdrop of the Letas' large family business: Zona Sul, a high-end grocer with 36 stores. Enrico's father, Fortunato, leads Zona Sul, but conflicts in Fortunato's generation resulted in the prohibition of Enrico's generation from joining that business. This led Enrico, his brother Patrick, and other cousins to launch independent food businesses that benefited from some of Zona Sul's resources. Enrico developed Yorgus within Patrick's premium cheese business, Vitalatte, and the brothers collaborate on strategic decisions for both brands. Now Enrico is considering taking Yorgus independent, in part to scale more quickly than his brother would be comfortable attempting. But Enrico must ponder the possible effects of such a move on the current operating arrangement with his brother's business, as well as on his relationship with his brother, his father, and the broader family. The case illustrates common family-enterprise challenges, including independence versus autonomy, shared decision-making, and the alignment of risk appetites.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Family-owned business enterprises -- Case studies; Corporate governance -- Case studies